PENERAPAN MODEL PEMBELAJARAN TEAM GAMES TOURNAMENT PADA PEMBELAJARAN EKONOMI - Hariroh, Siti; Sulistyarini, Sulistyarini; Buwono, Sri (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
Abstract This study aimed how to know implementasion in learning models Team Games Tournament( TGT ) and conventional learning models in improving student learning outcomes lesson Economy Class X SMA PGRI 1 Pontianak. Method used in this study is an experimental method using quasi experimental design with design research nonequivalent control group design . Subjects in this study were students of class X SMA PGRI 1 Pontianak with the number of 57students . Data collection tool used in this study is a direct observation sheet , achievement test documentation and paper work The results showed that the learning outcomes of the experimental class is higher than the control class for improving student learning outcomes larger experimental class is 75,60 while the control group only increased by 67,65. Keywoards: Teams Games Tournament, Learning Economy